Databases of L-shell X-ray intensity ratios for various elements after photon excitation - Zidi, A. (2024)
We gratefully acknowledge the support of the DGRSDT, Ministry of Higher Education and Scientific Research, Algeria . This work was done with the support of Mohamed El Bachir El Ibrahimi University , under project (PRFU) N o : B00L02UN340120230004 . This work was also supported by the Fundação para a Ciência e Tecnologia (FCT), Portugal through contract UID/FIS/04559/2020 (LIBPhys). S.C. warmly acknowledges the financial support of Lancaster University, and A.F. gratefully acknowledges the support of the Joint Research Centre of the European Commission. Publisher Copyright: © 2024 Elsevier Inc.